Studies on jackfruit seed starch as a novel natural superdisintegrant for the design and evaluation of irbesartan fast dissolving tablets - Vidyadhara Suryadevara; Sasidhar Reddyvallam Lankapalli; Lakshmi Harika Danda; Vijetha Pendyala; Vijetha Katta (Integrative Medicine Research)
Background: In the present investigation, an attempt was made to isolate starch from jackfruit seed powder and utilize it as a superdisintegrant to design fast dissolving tablets of irbesartan. Methods: Starch was isolated from jackfruit seeds via aqueous and alkali extraction processes and evaluated for its physicochemical properties, for phytochemical tests, and for acute toxicity studies. Irbesartan fast dissolving formulations were prepared using the wet granulation technique. Results: Acute toxicity studies for the extract indicated that all rats were healthy with no physiological changes in their behavior. The prepared irbesartan tablet formulations were found to be stable according to the Indian Pharmacopoeia-specified limits for postcompression parameters. From in vitro dissolution studies, it was observed that formulations F5 and F8 containing 5% w/w of alkali extracted starch and 5% w/w of croscarmellose sodium showed faster disintegration and improved dissolution rate compared with the other formulations. Fourier transfer infrared spectroscopic and differential scanning colorimetric analysis performed on optimized formulations indicated that there were no major interactions between the drug and excipients. Accelerated stability studies carried out on optimized formulations showed all tablets to be stable. Conclusion: The tablets prepared from jackfruit seed starch as superdisintegrant were found to be suitable for preparation of fast dissolving tablets.